Towards a full-scale CFD guideline for simulating a ship advancing in open water - Huang, Luofeng; Pena, Blanca; Thomas, Giles (Taylor & Francis, 2023)
Computational Fluid Dynamics (CFD) simulations of a ship’s operations are generally conducted at model scale, but the reduced scale changes the fluid behaviour around the ship. Whilst ideally ship simulations should be run directly at full scale, a guide has not been published to advise on the suitable setups that can provide accurate results while minimizing the computational cost. To address this, the present work explores an optimal approach for full-scale ship simulations. Extensive sensitivity studies were conducted on relevant computational setups to investigate their influences on the prediction of ship resistance, ship-generated waves as well as the boundary-layer flow of the hull. A set of CFD setups for full-scale ship simulations in open water was recommended. It was demonstrated that the ideal Y+ and Courant numbers in full scale are evidently different from those given in current model-scale CFD guidelines, indicating the necessity to establish full-scale CFD guidelines separately.
Keywords: Ship; full-Scale; computational fluid dynamics; guideline; resistance; boundary layer; wave; sea trial